Anesthetics Used In Therapeutic Dentistry (Texas Journal of Medical Science, 2023)
Effective local anesthesia is the basis for pain control in endodontics and therapeutic dentistry. Regardless of the doctor's skills, treatment and management of the patient are difficult or impossible without effective anesthesia. This chapter discusses the pharmacological properties of local anesthetics, the comparative advantages and limitations of various anesthetics and how they are administered. Other chapters of this article provide information on the use of local anesthetics in the diagnosis and treatment of patients with urgent conditions